Metal-Free Photoinduced Cascade Cyclization of Alkyne-Tethered N-Alkoxybenzamides - Tang, Ximei; Baoc, Chen; Cheng, Guang; Liao, Yuling; Xie, Wenlin; Qiu, Guanyinsheng (Synthesis, 2025)
In this work, a photoinduced synthesis of isoxazolidine-fused isoquinolin-1-ones and 3,4-dihydro[1,2]oxazino[2,3-b]isoquinolin-10(2H)-one from alkyne-tethered N-alkoxybenzamides is reported. The gram-scaled synthesis and structural elaboration of isoxazolidine-fused isoquinolin-1-ones are also realized. The reaction is promoted by an equimolar amount of tetrabutylammonium chloride, under metal- and catalyst-free conditions. In the reaction, it is believed that the alkyne-tethered N-alkoxybenzamide starting materials serve as photosensitizers, and the photoexcited substrate induces the formation of a chloro radical. The N-radical results from hydrogen atom abstraction by the chloro radical at the N–H bond of the substrates.
Keywords: photoinduced; metal-free; N-radical; quinolin-1-ones; cascade cyclization